Common ground: Addressing attrition across diverse institutions in higher education - Rebecca L. Jobe; Jim Lenio (Laureate Education Inc, 2014)
Student attrition is an ongoing concern in American higher education, where institutions are being increasingly held accountable for the success of the students they admit. While differences across diverse institutions exist, research suggests that there are many similarities regarding issues related to student persistence and success. In fact, this common ground presents an opportunity for common solutions. The variety of higher education institutions utilizing knowledge gained through institutional initiatives continues to identify new, better ways of serving students. This article sheds light on the known differences between institution types while recognizing the common goals of improving student persistence. The article further supports the need for additional research in this area to fully understand how the higher education community can best prepare and support students of all types, from all institutions, to reach their educational goals. DOI: 10.18870/hlrc.v4i2.209